Quenches across the self-organization transition in multimode cavities. (7th February 2018) - Keller, Tim; Torggler, Valentin; Jäger, Simon B; Schütz, Stefan; Ritsch, Helmut; Morigi, Giovanna
Abstract: A cold dilute atomic gas in an optical resonator can be radiatively cooled by coherent scattering processes when the driving laser frequency is tuned close to but below the cavity resonance. When the atoms are sufficiently illuminated, their steady state undergoes a phase transition from a homogeneous distribution to a spatially organized Bragg grating. We characterize the dynamics of this self-ordering process in the semi-classical regime when distinct cavity modes with commensurate wavelengths are quasi-resonantly driven by laser fields via scattering by the atoms. The lasers are simultaneously applied and uniformly illuminate the atoms; their frequencies are chosen so that the atoms are cooled by the radiative processes, and their intensities are either suddenly switched or slowly ramped across the self-ordering transition. Numerical simulations for different ramp protocols predict that the system will exhibit long-lived metastable states, whose occurrence strongly depends on the initial temperature, ramp speed, and the number of atoms.